Optimalisasi Penerapan Kelas Bilingual menuju Pembelajaran Efektif Di SMP Negeri 1 Dukun Gresik - Bambang Sugianto (Universitas Muhammadiyah Malang, 2014)
Bambang SugiantoGuru SMP Negeri 1 Dukun Gresike-mail:bamsririn@gmail.comAbstract:This research used a qualitative descriptive approach. The subjects in this research were school principals, curriculum division, teachers, and employees of State Junior High School 1 of Dukun Gresik and school committees. The data collection is obtained through observation, interviews, and documentation. While data analysis through descriptive analysis is implemented in three ways, they are: 1) data reduction, 2) display or the presentation of data, 3) Withdrawal of conclusion or verification. The validity of data in this research used the triangulation technique of data sources. Planning and learning in the classroom of State Junior High School 1 of Dukun have been prepared in accordance with The Regulation of National Education Minister Number 41 of 2007 and the characteristics of bilingual classroom learning. In bilingual classroom learning process, the implementation of the bilingual classroom learning on science and mathematics subjects in English language uses two learning models, which are separate learning model (parallel) and an integrated learning model (integrated). The assessment and supervision of learning outcomes of Bilingual classes in State Junior High School 1 of Dukun is implemented in accordance with the Ministerial Regulation number 41 of 2007Keywords: bilingual, learning mathematics and scienceAbstrak:.Penelitian ini menggunakan pendekatan deskriptif kualitatif. Adapun subyek dalam penelitian ini adalah kepala sekolah, urusan Kurikulum, guru, karyawan SMP Negeri 1 Dukun Gresik dan komite sekolah. Pengumpulan data melalui observasi, wawancara, dan dokumentasi. Sedangkan untuk menganalisa data melalui analisis deskriptif dilakukan dengan tiga cara, yaitu: 1) reduksi data, 2) display atau penyajian data; 3) Penarikan kesimpulan atau verifikasi. Keabsahan data dalam penelitian ini menggunakan teknik triangulasi sumber data. Perencanaan, pembelajaran di kelas SMP Negeri 1 Dukun telah disusun sesuai dengan Permendiknas nomor 41 tahun 2007 dan karakteristik pembelajaran kelas bilingual. proses pembelajaran kelas bilingual, sedangkan pelaksanaan pembelajaran kelas bilingual mata pelajaran IPA dan Matematika dalam bahasa Inggris menggunakan dua model pembelajaran yaitu model pembelajaran terpisah (parallel) dan model pembelajaran terpadu (integreted). Adapun penilaian dan pengawan hasil pembelajaran Kelas Bilingual di SMP Negeri 1 Dukun dilaksanakan sesuai dengan Permendiknas nomor 41 tahun 2007.Kata kunci: Bilingual, Pembelajaran Matematika dan IPA